2014
DOI: 10.1007/s13524-013-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grandparents on Children’s Schooling: Evidence From Rural China

Abstract: Whether or not the social class of grandparents affects grandchildren's socioeconomic outcomes net of the characteristics of the middle generation is much debated in the social mobility literature. Using data from the 2002 Chinese Household Income Project, we investigate the direct effects of grandparents on grandchildren's educational attainment in rural China. We find that the influence of grandparents is contingent on living arrangements. While the educational level of coresident grandparents directly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(201 citation statements)
references
References 44 publications
(49 reference statements)
10
189
1
1
Order By: Relevance
“…As was pointed out before, to the extent that independent grandparent effects are a result of socioemotional influence, or cultural inheritance, they require some level of proximity and interaction between grandparents and their children, while this is not as clear if they result from economic or biological factors (see Zeng and Xie 2014). As a sensitivity analysis we run interaction models including indicators of life status and residence (same parish) of G1 at the time of G3's birth.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As was pointed out before, to the extent that independent grandparent effects are a result of socioemotional influence, or cultural inheritance, they require some level of proximity and interaction between grandparents and their children, while this is not as clear if they result from economic or biological factors (see Zeng and Xie 2014). As a sensitivity analysis we run interaction models including indicators of life status and residence (same parish) of G1 at the time of G3's birth.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Socio-emotional factors or transmission of cultural capital, on the other hand, requires interaction between grandfather and grandson, which for most of the period covered in this study also presupposes residential proximity and that the grandfather is alive during the childhood of the grandson (Solon 2014;Zeng and Xie 2014). Increased longevity and improved health of older people, together with higher rates of union dissolution, also implies that the opportunity of direct influence from grandparents to grandchildren, through social or emotional influence via direct interaction, possibly has increased, and that the effect of this also should have grown over time (Bengtson 2001).…”
Section: Introductionmentioning
confidence: 99%
“…So far, there seems to be little empirical support for the idea that successful multigenerational transmission would depend on the quality of the personal relationship between grandparents and their grandchildren, as neither the analyses of Jaeger (2012) using U.S. data nor those of Bol and Kalmijn (2016) for the Netherlands yielded any positive evidence. Zeng and Xie's (2014) research on rural China instead suggests that geographical proximity Ziefle Persistent Educational Advantage may matter more, up to the point of multigenerational transmission occurring only for coresident grandparents in their study. Moreover, the evidence in both Jaeger (2012) and Møllegaard and Jaeger (2015) indicates that multigenerational advantage occurs mostly through cultural transmission, as they obtained the strongest effects for grandparents' level of education in both U.S. and Danish data.…”
Section: A Review Of Current Researchmentioning
confidence: 90%
“…Net grandparent effects on educational or occupational attainment have been reported for such a diverse set of countries as Denmark, Finland, Germany, Sweden, and the United Kingdom Boliver 2013, 2014;Modin, Erikson, and Vadero 2013;Hällsten 2014;Hertel and Groh-Samberg 2014;Lindahl et al 2015;Møllegaard and Jaeger 2015; but cf. Erola and Moisio 2007 for negative results in case of Finland), Zeng and Xie (2014) reported conditional net grandparent effects (for coresident grandparents only) for China, and only Bol and Kalmijn (2016) found no grandparent effects on attainment for the Netherlands after controlling for parental characteristics.…”
Section: Ziefle Persistent Educational Advantagementioning
confidence: 97%
“…Unfortunately, there is very little research in relation to the effect of grandparents on children's school experience in rural China. Only one Chinese study has specially focused on under the circumstance of rural area by Zeng and Xie (2014) who found that co-resident grandparents' educational level significantly influences the children's academic attainment. Although this lack of research connected with how grandparents value education and whether their perspective can influence their grandchildren or not, it is reasonable to assume that grandparents' perspective could be significantly influenced by communist ideology and traditional Chinese, because they impacted 'Planned Economy' and 'The Cultural Revolution' during Mao's period.…”
Section: Stakeholders' Perspectives On Educational Value In Rural Chinamentioning
confidence: 99%